Toxoplasma gondi infection in free-range chicken: mini-review and seroprevalence study in Oyo State, Nigeria (2012)
Free-range chickens are sentinels for the presence of Toxoplasma gondii oocysts in the environment because they feed from ground. T. gondii infected chickens are also an important source of infection for cats that shed environmentally resistant oocysts after eating infected chicken tissues. We surveyed 50 free-range chickens from Oyo State, Nigeria for the presence of T. gondii antibodies using the modified agglutination test (MAT). All chickens tested seropositive with MAT titers of 1:5 in 8 chickens, 1: 1:25 in 9 chickens, 1:100 in 19 chickens, and 1:500 in 14 chickens. Thus, even at a very conservative cut-off titer of 1:100, antibodies were found in 33 of 50 chickens, indicating a high prevalence of T. gondii in chickens.